Antioxidant status and hypoxia severity in various compensatory-adaptive reaction types among young men with mitral valve prolapse - S. A. Chepurnenko (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To assess antioxidant system (AOS) enzyme activity and red blood cell hypoxia severity, according to compensatory-adaptive reaction type in young men with mitral valve prolapse (MVP). Material and methods. In 137 young men with MVP, red blood cell activity of catalase (C), glutathione reductase (GR), superoxide dismutase (SOD), lactate, pyruvate concentration, lactate/pyruvate (L/P) coefficient were measured by standard methods, together with cardiohemodynamic parameters. Results. In Group I (high compensatory-adaptive potential), L/P was 2,2 times higher than in controls. In Group II (decreased compensatory-adaptive potential), this parameter was higher than in controls by 14,6% (p<0,05). In Group I, L/P was higher than in Group II by 93,8% (р<0,05). Comparing to control group, in Group I, C activity was 3,26 times lower, and SOD and GR activity was 3,99 and 2,03 times higher (p<0,05). C activity was 4,59 times lower, and SOD and GR activity was 6,23 and 1,85 times higher than in controls (p<0,05). In Group I, comparing to Group II, C and SOD activity was higher by 40,6% and 58,5%, respectively (p<0,05). Conclusion. In MVP patients, first-line AOS dysbalance and glutathionedependent mechanism strain were more manifested in Group II. Red blood cell aerobic metabolism predominance was of adaptive nature in Group I, being a factor of cell and tissue damage in Group II.